Pengaruh Green Product, Green Advertising, dan Green Price Terhadap Keputusan Pembelian Produk Tupperware (Studi Kasus Pada Konsumen Produk Tupperware di Magelang) - Azalia Azalia; Friztina Anisa (Borobudur Management Review, 2021)
This study aims to examine the effect of green products, green advertising, and green prices on purchasing decisions for tupperware products. The sample of this research is consumers who have bought Tupperware products. The sampling method used purposive sampling with a total sample of 100 respondents. The analytical tool used is multiple linear regression with the help of SPSS version 24.0. The results show that green products and green price have an positive effect and significant on purchasing decisions, green advertising have an positive effect but not significant on purchasing decisions.